Atomic‐Scale Insight into Exsolution of CoFe Alloy Nanoparticles in La0.4Sr0.6Co0.2Fe0.7Mo0.1O3−δ with Efficient CO2 Electrolysis. (25th June 2020) - Lv, Houfu; Liu, Tianfu; Zhang, Xiaomin; Song, Yuefeng; Matsumoto, Hiroaki; Ta, Na; Zeng, Chaobin; Wang, Guoxiong; Bao, Xinhe
Abstract: In situ exsolution of metal nanoparticles in perovskite under reducing atmosphere is employed to generate a highly active metal–oxide interface for CO2 electrolysis in a solid oxide electrolysis cell. Atomic‐scale insight is provided into the exsolution of CoFe alloy nanoparticles in La0.4 Sr0.6 Co0.2 Fe0.7 Mo0.1 O3− δ (LSCFM) by in situ scanning transmission electron microscopy (STEM) with energy‐dispersive X‐ray spectroscopy and DFT calculations. The doped Mo atoms occupy B sites of LSCFM, which increases the segregation energy of Co and Fe ions at B sites and improves the structural stability of LSCFM under a reducing atmosphere. In situ STEM measurements visualized sequential exsolution of Co and Fe ions, formation of CoFe alloy nanoparticles, and reversible exsolution and dissolution of CoFe alloy nanoparticles in LSCFM. The metal–oxide interface improves CO2 adsorption and activation, showing a higher CO2 electrolysis performance than the LSCFM counterparts. Abstract : The exsolution of CoFe alloy nanoparticles in La0.4 Sr0.6 Co0.2 Fe0.7 Mo0.1 O3− δ perovskite is investigated at atomic scale using in situ scanning transmission electron microscopy with energy dispersive X‐ray spectroscopy and density functional theory calculations.